2009
DOI: 10.1179/crn.2009.036
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Posture and Equilibrium and the Auriculotemporal Nerve In Patients with Disturbed Gait and Balance

Abstract: Balance is defined as a state of equilibrium or parity characterized by cancellation of all forces by equal opposing factors. This is the act of maintaining an upright posture (static balance) or in locomotion (dynamic balance or gait). This system depends on vestibular function, vision, and proprioception to maintain posture, to navigate in one's surroundings, to coordinate motion of body parts, to modulate fine motor control, and to initiate the vestibuloculomotor reflexes. These parts of the vestibular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…Our clinical observation supports the hypothesis that this group of patients may be suffering of undiagnosed TMJ disc dislocation, subsequent distal condylar displacement and associated compression and irritation of the AT nerve. We have shown that by treating the TMD and making changes in the maxillomandibular relationship with some type of a hard intraoral appliance or a neurocranial vertical distractor (NCVD) [18], we are not only effectingand treating the symptoms of pain and discomfort, but we also resolve symptoms of neurologic disorders, neuromuscular dysfunctions, and dystonia. Clinically, this is accomplished simply by removing the irritation or compression of the AT nerve, which serves the joint disc and capsule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our clinical observation supports the hypothesis that this group of patients may be suffering of undiagnosed TMJ disc dislocation, subsequent distal condylar displacement and associated compression and irritation of the AT nerve. We have shown that by treating the TMD and making changes in the maxillomandibular relationship with some type of a hard intraoral appliance or a neurocranial vertical distractor (NCVD) [18], we are not only effectingand treating the symptoms of pain and discomfort, but we also resolve symptoms of neurologic disorders, neuromuscular dysfunctions, and dystonia. Clinically, this is accomplished simply by removing the irritation or compression of the AT nerve, which serves the joint disc and capsule.…”
Section: Resultsmentioning
confidence: 99%
“…The proper maxillomandibular relationship affects this complex system. When the trigeminal signals are produced properly it effects all the cross over fibers of the brain stem, thus causing the changes/improvements measured in movement disorder patients (i.e., tics and tremors decrease or stop immediately, correcting of the head posture or position, release of tension in the face, strengthening of upper body, gait and balance improvement, and release of neck tension) [18]. …”
Section: Discussionmentioning
confidence: 99%
“…If in group I we can state that the clenching worsens the algic symptomatology in charge ofthe cranio-cervical muscle, which was already suffering from the post-traumatic period; for the patients from group 2 the stomatognathic structures appear to be already suffering and the trauma worsens an already dysfunctional condition: indeed clenching causes an excess ofTMJ pressure aggravating and resulting with the manifestation of a algic-dysfunctional pathology (indirect lesive action), which was already present and apparently compensated for. It needs to be mentioned that this articulation might be already suffering due to the trauma (direct lesive action) due to the typical abrupt whiplash cranio-cervical movement (13,14). The postural facts obtained during the present study show therefore the extreme importance of the stomatognathic system in the neurophysiologic management of the postural: in fact the patients with malocclusion present clearly worse postural conditions in comparison to the patients from group I (without malocclusion), with statistically significant differences (table 3); moreover the differences in between the two groups of patients leans to reduce noticeably in the tests done with occlusal deviation by improving the performances viewed in group 2 (in comparison to the normal occlusion tests), and by a visible worsening of group I.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether there is any relationship between TMD and coxalgia. A relationship between TMD and posture [2] and that between posture and gait movement disorders including temporomandibular joint disorders (TMJD) has been reported [3]. Therefore, it is important to investigate the relationship between TMDs and coxalgia.…”
Section: Introductionmentioning
confidence: 99%